Delivering your daily dose of well-being to the workplace: a randomized controlled trial of an online well-being programme for employees. Issue 4 (4th July 2017) - Neumeier, Lena M.; Brook, Libby; Ditchburn, Graeme; Sckopke, Philipp
ABSTRACT: The purpose of this study was to evaluate a newly developed brief, cost-effective, flexible, and broadly accessible online programme designed to enhance employee well-being. Considering the demands of the working world, the development of the positive intervention (PI) programme was based on empirical findings and latest theoretical advances from the field of positive psychology, namely the PERMA model of well-being. The new PERMA-based programme's effectiveness to increase employee well-being was evaluated with a longitudinal field experiment, including a wait list control group and an already established PI programme (i.e., gratitude programme) for comparison (three-armed randomized controlled trial; n = 303, N male = 99, N female = 203, M age = 41.16, SD = 12.26). Repeated measures analyses of variance (ANOVAs) supported that on average, participants of the gratitude programme and the PERMA-based programme reported significant increases in employee well-being after the intervention, as compared to no increases in the wait list control group. The significant increases yielded small effect sizes for general subjective well-being and medium effect sizes for work-related subjective well-being. Post-hoc analyses controlling for baseline well-being also supported the efficacy of the PIs. Contrary to the prediction of the PERMA-based programme's superiority, participants of both online PI programmes reported similar gains in employee well-being components. Practical implications, limitations, and future research are discussed.